Therapeutic potential of mesenchymal stem cell-derived microvesicles - Biancone, Luigi; Bruno, Stefania; Deregibus, Maria Chiara; Tetta, Ciro; Camussi, Giovanni (Nephrology, dialysis, transplantation, 2012)
Several studies have demonstrated that mesenchymal stem cells have the capacity to reverse acute and chronic kidney injury in different experimental models by paracrine mechanisms. This paracrine action may be accounted for, at least in part, by microvesicles (MVs) released from mesenchymal stem cells, resulting in a horizontal transfer of mRNA, microRNA and proteins. MVs, released as exosomes from the endosomal compartment, or as shedding vesicles from the cell surface, are now recognized as being an integral component of the intercellular microenvironment. By acting as vehicles for information transfer, MVs play a pivotal role in cell-to-cell communication. This exchange of information between the injured cells and stem cells has the potential to be bi-directional. Thus, MVs may either transfer transcripts from injured cells to stem cells, resulting in reprogramming of their phenotype to acquire specific features of the tissue, or conversely, transcripts could be transferred from stem cells to injured cells, restraining tissue injury and inducing cell cycle re-entry of resident cells, leading to tissue self-repair. Upon administration with a therapeutic regimen, MVs mimic the effect of mesenchymal stem cells in various experimental models by inhibiting apoptosis and stimulating cell proliferation. In this review, we discuss whether MVs released from mesenchymal stem cells have the potential to be exploited in novel therapeutic approaches in regenerative medicine to repair damaged tissues, as an alternative to stem cell-based therapy.